Analisis Perbandingan CP/TP dan KI/KD pada Modul Ajar Matematika Kurikulum Merdeka di SMAN 16 Padang (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research was conducted to examine in depth what are the main differences between the Learning Outcomes (CP) and Learning Objectives (TP) in the Merdeka Curriculum compared to the Core Competencies (KI) and Basic Competencies (KD) in the 2013 Curriculum. The main focus is on how this affects the development and implementation of mathematics teaching modules in phase E, especially in SMA Negeri 16 Padang. The research method used was qualitative research involving direct observation at the school, conducting in-depth interviews, and reviewing documents related to various teaching modules. From the analysis, it can be seen that the structure of CP and TP is more integrative, contextual, and flexible compared to the structure of KI and KD which tend to be separate and procedural in nature. In addition, teaching modules based on Merdeka Curriculum encourage the development of the Pancasila Student Profile and 21st century competencies. This conclusion has a major influence on curriculum development and learning designs that are more adaptive to student needs and the times.